Generating high confidence contracts without user input using Daikon and ESC/Java2 - Rayakota, Balaji (Kansas State University, 2013)
Invariants are properties which are asserted to be true at certain program points. Invariants are of paramount importance when proving program correctness and program properties. Method, constructor, and class invariants can serve as contracts which specify program behavior and can lead to more accurate reuse of code; more accurate than comments because contracts are less error prone and they may be proved without testing. Dynamic invariant generation techniques run the program under inspection and observe the values that are computed at each program point and report a list of invariants that were observed to be possibly true. Static checkers observe program code and try to prove the correctness of annotated invariants by generating proofs for them. This project attempts to get strong invariants for a subset of classes in Java; there are two phases first we use Daikon, a tool that suggests invariants using dynamic invariant generation techniques, and next we get the invariants checked using ESC/Java2, which is a static checker for Java. In the first phase an ‘Instrumenter’ program inspects Java classes and generates code such that sufficient information is supplied to Daikon to generate strong invariants. All of this is achieved without any user input. The aim is to be able to understand the behavior of a program using already existing tools.
Keywords: Software Contracts; Automatic Invariant Generation; Daikon; ESC/Java2; Computer Science (0984)